Prevalence and clonal lineages of biofilm-producing Staphylococcus aureus from clinical samples and healthcare workers at Ahmadu Bello University Teaching Hospital, Nigeria - Umar, Kabir; Abdullahi, Idris Nasir; Magashi, Abdulkadir Magaji; Kawo, Abdullahi Hassan; Usman, Yahaya; El-fulaty Ahmad, Abdurrahaman; Torres, Carmen (German Medical Science GMS Publishing House, 2024)
This study determined the frequency and molecular features of from 206 burn and wound patients (BWPs) as well as 94 healthcare workers (HCWs) at the Ahmadu Bello University Teaching Hospital, Zaria, Northern Nigeria. Nine (4.4%) and five (5.3%) samples from BWPs and HCWs were identified as S positive, respectively. Seven (50%) were -positive (associated with SCC types IVa and V), while 35.7% presented a multidrug resistance (MDR) phenotype. The isolates belonged to 11 diverse types, including three new (t4539, t6043, t11694) and one singleton (t779), which were assigned to four clonal complexes. Two and three carrying strains were identified. All the isolates were moderate biofilm producers with diverse combinations of the biofilm and regulatory genes. The detection of genetically diverse lineages and toxigenic strains highlights the need for improved surveillance of resistant and pathogenic strains in healthcare facilities.